Analysing traffic elements in International Islamic University Malaysia by revealed preference approach - Kadar Hamsa, Abdul Azeez (2012)
University campuses should create peaceful and pleasant learning environment for the benefits of campus community. The degree of transport use on-campus by both staff and student population is very important to achieve this noble target. It has been observed in the recent past that the alarming vehicle growth in the University would eventually not only exert tremendous pressure on the road and other traffic related infrastructure but also induce detrimental effects on learning environment. The purpose of this paper is to highlight the perceptions of IIUM community on existing traffic elements conditions including parking and bicycle use in IIUM Gombak campus. Questionnaire survey was administered targeting academic, administrative and student population on-campus. About 389 (33%) filled-in questionnaires were collected from staffs and 775 (67%) from students. The findings on the perceptions of IIUM community on traffic elements conditions in IIUM including parking provisions, pedestrian circulation system and bicycle use are highlighted in this paper. Discussion on issues related to traffic flow on-campus and conclusions are also drawn.